Children of the river - Crew, Linda (New York : Delacorte Press, 1989)
Having fled Cambodia four years earlier to escape the Khmer Rouge army, seventeen-year-old Sundara is torn between remaining faithful to her own people and enjoying life in her Oregon high school as a "regular" American.
Keywords: Asian Americans -- Fiction; Khmers -- Fiction